PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN YANG TERDAFTAR DALAM INDEKS LQ45 DI BURSA EFEK INDONESIA - CHALIK, DAVID (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2024)
This study aims to analyze the effect of profitability and leverage on firm value for companies listed on the LQ45 Index on the Indonesia Stock Exchange (IDX). The LQ45 Index comprises 45 selected companies representing high liquidity and large market capitalization on the IDX. The sampling technique used is purposive sampling, resulting in 27 companies as the sample during the period from 2020 to 2024. The sample selection criteria are based on the completeness of financial data and the consistency of the companies on the LQ45 Index throughout the study period. This research employs a quantitative descriptive method to illustrate the relationship between the examined variables. The data is analyzed using EViews version 13. The analysis results indicate that profitability has a positive and significant impact on firm value, with a regression coefficient of β1 = 2.401250 and a p-value of 0.000, meaning an increase in profitability by 1 unit can enhance firm value by 2.401250. Conversely, leverage does not have a significant effect on firm value, with a regression coefficient of β2 = 2.692045 and a p-value of 0.49, suggesting that the level of leverage does not play a significant role in determining firm value during the analyzed period. The R-squared value of 0.83 indicates that 83% of the independent variables have a high influence on firm value. This study provides important insights for financial managers and investors in making decisions related to company strategies